HARMONISASI KODE ETIK PROFESI GURU DENGAN UNDANG-UNDANG NOMOR 14 TAHUN 2005: SUATU KAJIAN YURIDIS NORMATIF - Salsabila, Elmira; Solehuddin, M. Sugeng; Rahmawati, Niken (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Teacher professionalism is determined not only by the mastery of competencies but also by adherence to legal norms and the professional code of ethics. The rise in cases involving teachers such as the